Influence of perception on green products towards green purchase intentions / Mohamad Saiful Azmi Hambali - Hambali, Mohamad Saiful Azmi (Faculty of Business and Management, 2019)
The aim of this research is to study the influence of perception on green products towards green purchase intentions. This research is based on sample of 76 respondents where the respondents is student of BBA(Hons) Marketing from Universiti Teknologi Mara, Cawangan Melaka, Kampus Bandaraya Melaka. From the results of this research, it shows that only green product value and green advertising have significant influence on green purchase intentions while others variable which is green packaging, eco-label and green corporate perception have negative result in influence on green purchase intentions. In recent decades, environmental issues have been widely recognized and discussed. The lack of knowledge and concern towards environment creates harmful situation in Malaysia and around the world and many issues about environment was happen day by day such as pollution, death of animal and many more. Thus, the main objective of this research is to identify which variables (green packaging, green product value, eco-label, green corporate perception and green advertising) have impact on green product influencing on green purchase intention. Sampling technique used for this research is Simple random sampling technique due to probability sampling method used. From the finding, green product value and green advertisement have positive significant relationship on green purchase intention while the other variables (green packaging, eco-label, green corporate perception) has negative relationship. The most influential factor on green purchase intention are green product value.